Boosting neuregulin 1 type-III expression hastens SMA motor axon maturation - Lingling Kong; Cera W. Hassinan; Florian Gerstner; Jannik M. Buettner; Jeffrey B. Petigrow; David O. Valdivia; Michelle H. Chan-Cortés; Amy Mistri; Annie Cao; Scott Alan McGaugh; Madeline Denton; Stephen Brown; et al. (Acta Neuropathologica Communications, 2023)
Abstract Intercellular communication between axons and Schwann cells is critical for attaining the complex morphological steps necessary for axon maturation. In the early onset motor neuron disease spinal muscular atrophy (SMA), many motor axons are not ensheathed by Schwann cells nor grow sufficiently in radial diameter to become myelinated. These developmentally arrested motor axons are dysfunctional and vulnerable to rapid degeneration, limiting efficacy of current SMA therapeutics. We hypothesized that accelerating SMA motor axon maturation would improve their function and reduce disease features. A principle regulator of peripheral axon development is neuregulin 1 type III (NRG1-III). Expressed on axon surfaces, it interacts with Schwann cell receptors to mediate axon ensheathment and myelination. We examined NRG1 mRNA and protein expression levels in human and mouse SMA tissues and observed reduced expression in SMA spinal cord and in ventral, but not dorsal root axons. To determine the impact of neuronal NRG1-III overexpression on SMA motor axon development, we bred NRG1-III overexpressing mice to SMA∆7 mice. Neonatally, elevated NRG1-III expression increased SMA ventral root size as well as axon segregation, diameter, and myelination resulting in improved motor axon conduction velocities. NRG1-III was not able to prevent distal axonal degeneration nor improve axon electrophysiology, motor behavior, or survival of older mice. Together these findings demonstrate that early SMA motor axon developmental impairments can be ameliorated by a molecular strategy independent of SMN replacement providing hope for future SMA combinatorial therapeutic approaches.